“The Role Of Paramedics In Pre-Hospital Decision-Making And Advanced Clinical Interventions: A Systematic Review” (The Review of Diabetic Studies, 2025)
The evolving role of paramedics in pre-hospital emergency care has transformed them from basic transport providers into highly skilled autonomous clinicians capable of performing critical decision-making and advanced medical interventions at the point of care. This systematic review examines the impact of paramedic-led pre-hospital decision-making and advanced clinical procedures on patient outcomes across trauma, cardiac, respiratory, and neurological emergencies. A comprehensive search of peer-reviewed literature from 2015 to 2024 was conducted across major databases including PubMed, Scopus, CINAHL, and Web of Science. Studies were included if they evaluated the effectiveness, accuracy, and clinical impact of autonomous decision-making or advanced interventions performed by paramedics. Findings indicate that paramedics who are empowered with advanced clinical training and decision support tools significantly improve survival rates, reduce treatment delays, and enhance pre-hospital patient stabilization. Interventions such as rapid sequence intubation, point-of-care ultrasound, pre-hospital thrombolysis, and ECG-based cath-lab activation demonstrate measurable effectiveness in critical time-sensitive conditions. Moreover, evidence highlights that paramedic decision-making autonomy, when supported by clear protocols and technological tools, leads to faster triage and better clinical outcomes. This review underscores the essential role of paramedics as frontline clinical leaders in modern healthcare systems and calls for expanded scope of practice, continuous training, and policy support to further enhance their effectiveness in pre-hospital care.